Prevalence of gastrointestinal parasitism in bovines of Cesar state, Colombia - Pinilla, Juan Carlos (2018)
The objective of the study was to determine the prevalence of gastrointestinal parasites in bovines from the department of Cesar, Colombia. Faecal samples were collected (n=862) from 27 dual-purpose cattle farms in two municipalities. The animals were stratified into three age groups: 0-12, 12-24 and >24 months. The samples were processed using the coprological techniques of McMaster, Dennis and Baermann. The genera of the parasites were identified according to the morphology of their eggs or infective larvae. The overall prevalence of gastrointestinal parasites was 83.2%, with the highest values for Eimeria sp (77.9%), Strongyloides sp (10.8%) and Haemonchus sp (8.5%). No statistical association was found due to effect of the municipalities, but it was observed due to the effect of the age group on the prevalence of Eimeria sp, Strongyloides, Haemonchus and Trichostrongylus (p<0.05).